Art and craft of harappans - Sharma, Deo Prakash (New Delhi : Kaveri Books, 2014)
Contents: Preface. 1. Introduction of Harappan civilization. 2. Harappans excavated sites in north-west South Asia. 3. Harappan script. 4. Catalogue of seals, sealings and copper tablets. 5. Handlist of Harappan seals and sealing. 6. Harappan mineral sites in north west south Asia. Bibliography. Index. This work is a masterpiece on archaeological material related to Harappan sites, belonging to both Indian and Pakistan. It provides an exclusive documentation of Harappan artifacts and other articles as found in various sites of one of the most ancient civilization of the world. The contents of the material provided herein sprawl from the excavated sites in the north west south Asia, including mineral sites in the region to script to seals, sealing and tablets and last, but not the least, to different types of objects discovered. The book gives a vivid and lucid description of the settlements, miniature figurines made up of stone/bronze/ceramic, pottery, terracotta articles, jewellery along with appropriate and eye catching illustrations and details which are easy to comprehend and remember. Not only this, the author has even touched on the subject of varied trys, tools implements and weapons existing in that period apart from delving in the than prevailing religious rituals. This pictorial presentation is not only valuable for a student of ancient history but also for all those who have tendency towards and taste for peeping into the annals of the hoary past.
Bibliography 222-232p.; Index 233-238p.
Keywords: Harappan civilization; Harappan script